Calpain Protease Causes Hypoxia-Induced Proteolysis in Cultured Human Retina. (April 2014) - Azuma, Mitsuyoshi; Hammond, Katherine B.; Nakajima, Emi; Shearer, Thomas R.
Abstract Purpose/Aim: Calpain proteases are known to be involved in retinal cell death in animal models. The purpose of the present study was to test for calpain activation in human retinas cultured under hypoxic conditions. Materials and Methods: Calpain activation was detected by immunoblotting for calpain substrates in human and monkey retinas cultured in gas generating pouches to reduce oxygen. Results: Hypoxia caused activation of calpains as measured by accumulation of the calpain-specific 145 kDa α-spectrin breakdown product. Opsin-1 (photoreceptor marker) and vimentin (Müller cell marker) were degraded. Calpain inhibitor SNJ-1945 ameliorated these changes. Results were similar to comparative data from cultured monkey retinas. Conclusions: In cultured human retina, hypoxia caused activation of calpain and subsequent proteolysis of critical substrates. The efficacy of SNJ-1945 in ameliorating these changes indicated that it might be useful to test as a drug for protecting against pathologic proteolysis of photoreceptor and Müller cells.